The impact of economic blockade on the performance of Qatari Islamic and conventional banks: a period-and-group-wise comparison - Abdilatif Mao Ali (ISRA International Journal of Islamic Finance, 2020)
Purpose: This paper aims to empirically assess the performance of Islamic banks (IBs) and conventional banks (CBs) in Qatar before and after the imposition of the economic blockade on Qatar and the significance of the blockade's subsequent impact. Design/methodology/approach This study focuses only on the domestic commercial banks comprising four IBs and five CBs operating in Qatar. The banks' financial reports are used as a secondary source to generate data. A study period from 2015 to 2019, separated into pre-blockade and post-blockade periods and comprising data on a semi-annual basis, was examined. Financial ratios and t-tests are used to compare bank performance and test the significance level of the blockade, respectively. Findings Generally, the findings show that IBs slightly outperformed CBs. Solvency ratios show strong capitalization (measured by capital adequacy ratio, CAR) and external fund (measured by equity multiplier ratio, EMR) reliance of the banks, despite minor fluctuations. Yet, only the CAR of CBs has been significantly affected by the blockade. Profitability (measured by return on assets, ROA and return on equity, ROE) of both bank groups grew unsteadily over the period, but IBs remained more efficient (measured by operating efficiency, OEOI) than CBs. Liquidity ratios indicate almost similar depositor fund utilization (measured by loans to deposit ratio, LDR) and credit offering (measured by loans to assets ratio, LAR) by the banks. All three metrics were weakly impacted. In terms of asset quality, bad loans (measured by non-performing loans ratio, NPL) and provisions (measured by loan loss provisions, LLP) surged moderately post-blockade. The blockade affected both groups' asset quality. Originality/value To the author's knowledge, this is the first study to comparatively examine the performance of Qatari IBs and CBs during the latest economic embargo and their exposure to the crisis.
Keywords: 330; Banking sector; Economic blockade; Financial ratios; Performance